2020
DOI: 10.1101/2020.07.20.20157743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low Seroprevalence of SARS-CoV-2 in Rhode Island Blood Donors Determined using Multiple Serological Assay Formats

Abstract: Epidemic projections and public health policies addressing Coronavirus disease (COVID)-19 have been implemented without data reporting on the seroconversion of the population since scalable antibody testing has only recently become available. We measured the percentage of severe acute respiratory syndrome- Coronavirus-2 (SARS-CoV-2) seropositive individuals from 2,008 blood donors drawn in the state of Rhode Island (RI). We utilized multiple antibody testing platforms, including lateral flow immunoassays (LFAs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Our findings are also in line with previous studies which showed that early in the pandemic the seroprevalence of Covid-19 in blood donors or other nontargeted populations was very low ranging from 0% to 2.0% (Erikstrup et al, 2021, Godbout et al, 2020, Qutob et al, 2020, Xu et al, 2020, Ho et al, 2020, Banjar et al, 2021, Nesbitt et al, 2021Slot et al, 2020, Fiore et al, 2021, Saeed et al, 2021). However other studies especially those from hardly hit communities early in the pandemic showed relatively high rates up to 23% (Percivalle et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are also in line with previous studies which showed that early in the pandemic the seroprevalence of Covid-19 in blood donors or other nontargeted populations was very low ranging from 0% to 2.0% (Erikstrup et al, 2021, Godbout et al, 2020, Qutob et al, 2020, Xu et al, 2020, Ho et al, 2020, Banjar et al, 2021, Nesbitt et al, 2021Slot et al, 2020, Fiore et al, 2021, Saeed et al, 2021). However other studies especially those from hardly hit communities early in the pandemic showed relatively high rates up to 23% (Percivalle et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Among the populations tested are healthy blood donors (Sughayer et al, 2020, Slot et al, 2020, Daniel J. Nesbitt et al, 2021, Gallian et al, 2020, Olariu et al, 2021, Younas et al, 2020, Banjar et al, 2021, Uyoga et al, 2021, Busch and Stone, 2021, Martinez-Acuña et al, 2020, Saeed et al, 2021, Slot et al, 2020, Fiore et al, 2021). Again the seroprevalence among healthy blood donors and other population groups studied varied according to the community tested and the time of testing in terms of the pandemic evolution (Lai et al, 2020, Rostami et al, 2020)…”
Section: Introductionmentioning
confidence: 99%
“…These attack rate estimates use symptomatic case data through September 6, as an infection on August 31 would have its mean time of symptoms occurrence six days later. The Rhode Island attack rate is able to be validated with a 2.2% late-April attack-rate estimate obtained from a household sero-survey [30] and 0.6% early-April estimate from blood donors [31] (population biased towards healthier individuals). Our Pennsylvania-wide attack rate has a Philadelphia early-April estimate of 3.2% as a comparator [32], as well as a 6.4% estimate from July using serum from dialysis patients (not adjusted for race or socio-economic indicators, and thus biased upward) [33].…”
Section: Resultsmentioning
confidence: 99%
“…The overall seroprevalence in New York City, at the peak of the epidemic, was estimated to be 21% with some communities as high as 68% using data from emergency care clinics [ 27 ]. This is juxtaposed to neighboring states, such as Rhode Island, where we estimated seroconversion to be 0.6% among blood donors in May 2020 [ 28 ]. Given the early introduction of SARS-CoV-2 in the NYC Metro area in March of 2020 as an initial, and possibly largest, ‘hot-spot’ in the United States, the estimated seroprevalence in this study may be lower than anticipated due to naturally waning antibody titers [ 29 ] (or due to demographics of donor population relative to the NYC population.…”
Section: Discussionmentioning
confidence: 99%